The Impact of Parental Involvement on the Educational Development of Students with Autism Spectrum Disorder - José Fernández Cerero; Marta Montenegro Rueda; Eloy López Meneses (MDPI AG, 2024)
Background/Objectives: Parental involvement is vital for the academic success and overall development of students, particularly those with Autism Spectrum Disorder (ASD), who face unique educational challenges. This study investigates the influence of parental involvement on the academic performance and school adjustment of students with ASD, focusing on the interplay of cultural identity and first language in their educational and social growth. The research also seeks to identify the challenges parents face and the strategies they use to support their children. Method: Employing a qualitative, interpretive approach, this study involved 42 parents of secondary school students with ASD in Seville, Spain. Data collection included in-depth interviews and focus group discussions, allowing for a comprehensive understanding of parental experiences. Results: The study found that active parental involvement greatly enhances students' academic performance and emotional well-being. Key strategies include creating structured home environments, utilizing assistive technologies, and fostering open communication with school staff. However, parents reported significant challenges, including limited school resources, communication barriers with educators, and a lack of ASD-specific training for teachers and parents. These challenges often hinder their ability to fully support their children's education. Conclusions: Active parental involvement is crucial for the educational success of students with ASD. The findings highlight the need for improved communication between schools and families, increased resources, and targeted ASD training for both teachers and parents. Additionally, the study advocates for greater investment in assistive technologies to better support students with ASD. Addressing these needs could significantly improve the educational experiences and outcomes for these students.